Coconut: Natural Source of Potential Anti Cancer Agent - Ghosh, Amit (International Coconut Community, 2016)
The current strategy of drug development is time consuming and expensive. This contrasts sharply with the vision of affordable drug development. The costly and the lengthy paradigm of drug discoveries are major obstacles for combating with rapidly emerging and sporadic diseases. The dichotomy between the urgent requirement of affordable treatment development and the hindrance it faces is apparent in several recent literatures which reflects the importance of drug repurposing and development of botanical drugs. Consistent with this idea, past few decades of studies on Cocos nucifera has yielded a fair knowledge about the anticancer potential of coconut products. The aggregate knowledge is undeniably positive and offers the novel avenues for the therapeutics and affordable drug development. This article highlights the link between coconut products and its anticancer effects.